Going beyond appearance: women inmates´stories - Deza Villanueva, Sabina (2007)
This is a pilot research study to identify some psychosocial factors associated with the criminal conduct, present in the life stories of 50 women, imprisoned in a Women Jail of Lima for having committed three criminal acts modalities: 8 for homicide, 12 for robbery, and 30  for drug dealing, with backgrounds of having suffered at least 10 years of family violence. As the investigation is part of a more extensive study on family violence and women ‘criminal conduct modality.